Molecular detection of Isoniazid, Rifampin and Ethambutol resistance to M. tuberculosis and M. bovis in multidrug resistant tuberculosis (MDR-TB) patients in Pakistan. (September 2017) - Munir, Saba; Mahmood, Nasir; Shahid, Saman; Khan, Muhammad Idrees
Abstract: The various aspects of MDR-TB, type of pathogen, different drug sensitive methods and mutation (s) in specific genes were determined. The histone-like protein ( hupB ) gene of M. tuberculosis was targeted by using primer sets: N & S and M & S (produced 645 bp & 318 bp fragment respectively). The most significant risk factors were the poverty and male gender of ages 11–25 years. All samples were detected as M. tuberculosis . By Drug Proportion method, the highest percentage (37%) was found resistant to only Rifampin. By MGIT method, the highest percentage (82.2%) was found resistant with the triple combination (Rifampin-RIF + Isoniazid-INH + Ethambutol-EMB) of the drugs. The highest mutations (76.92%) were found in gene rpoB (codon 531) in MDR TB patients. By, MAS-PCR, the highest percentage (34%) were found resistant to combination (INH + RIF) of the drugs. Minimum samples were resistant to RIF and RIF + INH drugs by MGIT, while proportionate results were observed from MAS-PCR and DP. Moreover, by MAS-PCR mutation in gene embB (306) caused EMB resistance (51.64%). We found that M. tuberculosis was the main cause of MDR-TB. Our findings may further be used for an early diagnosis of multi-drug resistant tuberculosis. Highlights: The histone-like protein ( hupB ) gene of M. tuberculosis was targeted by using two primer sets. By Drug Proportion method, the highest percentage (37%) was found resistant to only RIF. By MGIT method, the highest percentage (82.2%) was resistant with the triple combination of drugs. The highest mutations (76.92%) were found with gene rpoB (531). By MAS-PCR mutation in gene embB (306) caused EMB resistance (51.64%).